A Comparative Analysis of the Issues Related to Fintech Development in Kazakhstan and China - Patashkova, Yelena; Serikova, Madina; Margatskaya, Galina (Comparative Economic Research. Central and Eastern Europe, 2023)
The relevance of fintech development in Kazakhstan is evident due to the ever‑growing role of financial technologies not only there but also worldwide. This expansion is closely tied to the progress of electronic commerce and advertising, technical development, socio‑demographic changes, and social development. The article identifies problem areas of fintech development in Kazakhstan and provides practical methods for solving them. The main research method is structural‑analytical, which combines all the problem areas of fintech into structural units and considers their importance. A forecasting method is also applied to predict certain scenarios of fintech development in Kazakhstan. The practical methods of solving the issues related to fintech development can be characterised as methodological, analytical, informative, effective, and predictive. The predictive component made it possible to determine the obstacles in fintech development and ways to achieve results. The results are of great importance due to the relevance of fintech in Kazakhstan. Although it is likely to develop well, there are numerous obstacles, both public and private, and the measures for overcoming the problematic areas will be important and effective. Given the country’s advantages, Kazakhstan is capable of becoming a leader in financial technology start‑ups.